Lessons learned: Living Lab for People in a conflict affected setting in Colombia - Vanegas Cubillos, Martha Cristina; Rodríguez Ramírez, Luz Angela; Maya Vélez, Diana Lucía; Clavijo Ponce, Neidy Lorena; Guáqueta Solorzano, Victoria Eugenia; Buitrago Rueda, Juliana; Álvarez Ramírez, Javier Eduardo; Gómez Pineda, Thomas Enrique (2023)
The report details the establishment of a Living Lab for People (LL4P) in La Montañita, Colombia, as part of the Low-Emission Food Systems (Mitigate +) initiative, which seeks to transform food systems and address climate change impacts. The LL4P focuses on empowering key stakeholders, particularly women, youth, and marginalized groups, to enhance their capacity to implement low-emission sociotechnical innovations in the food system, emphasizing cattle/dairy and cacao value chains. Lessons learned underscore the critical role of building trust, active inclusion of women and youth, gender-transformative approaches, integration into local processes, a bottom-up approach, and a flexible, context-specific model. Challenges, including low public sector participation and exhaustion from interventions, are addressed through ongoing engagement, consultation, and transparent communication. In conclusion, the report emphasizes that the LL4P in Colombia has the potential to serve as a dynamic platform for co-designing low-emissions food systems and fostering peace in the region.